Therapeutic roles of a natural herbal product on ameliorating hepatic steatosis via gut dysbacteriosis modulating in treatment of nonalcoholic fatty liver disease in mice - Xiaoan Ren; Dewei Ye; Wei He; Xiaoqin Wu; Jiao Guo (Elsevier, 2021)
Background: The gut microbiota has well documented as an important player in mediating the development of nonalcoholic fatty liver disease (NAFLD). A patent natural herbal product, compound (Fufang) Zhenzhu Tiaozhi Capsule (FTZ), composed of eight Chinese medical herbs, has prescribed for the prevention and treatment of hyperlipidemia and NAFLD in China for over a decade. Aim of the study: To investigate gut microbiota-modulated therapeutic potential of FTZ on mice models of NAFLD. Methods: HPLC analysis performed for identifying and quantifying phytochemical constituents of FTZ. The therapeutic potentials on NAFLD were assessed by hepatic histological examination and biochemical assays of liver enzymes. The composition of the gut microbiota was analyzed by 16S rRNA sequencing. Lipid synthesis-related genes were detected using real-time quantitative polymerase chain reaction (RT-qPCR). Correlations differentially regulated bacterial taxa mediated by FTZ intervention and the clinical parameters of NAFLD obtained by Spearman's correlation analysis. Results: Significantly therapeutic potentials on dysbiosis of the gut microbiota modulating in high-fat and high-cholesterol (HFHC) diet-induced mice models of NAFLD revealed after FTZ intervention. Downtrends of abnormal parameters of NAFLD characterized by increased body weight (BW), fat contents, levels of total cholesterol (TC), triglyceride (TG) both the serum and liver tissue of the mice, and the activities of alanine aminotransferase (ALT), aspartate transaminase (AST) shown after FTZ intervention. Meanwhile, the over expressions of lipid synthesis-related genes in mice were down-regulated after FTZ treatment. FTZ modulated the gut microbiota composition, which increased the abundance of Bacteroidetes and reduced the ratio of Firmicutes/Bacteroidales indicated by 16S rRNA sequence data analysis. Parallelly, the increased abundance of Bacteroidetes significantly correlated with down-regulated expressions of lipogenic genes of SCD1, FAS, CD36 and C/EBP-α by FTZ intervention. Conclusion: Natural herbal product of FTZ attenuated hepatic steatosis via modulating the gut microbiota in mice models of NAFLD, the pathway of FTZ down-regulated expressions of lipogenic genes of SCD1, FAS, CD36 and C/EBP-α, thereby inhibiting liver fat biosynthesis, is considered one of the important mechanisms of FTZ in preventing and treating NAFLD.